Using Predicted Atherosclerotic Cardiovascular Disease Risk for Discrimination of Awake or Nocturnal Hypertension. (13th July 2020) - Sakhuja, Swati; Booth, John N; Anstey, David E; Jaeger, Byron C; Lewis, Cora E; Lloyd-Jones, Donald M; Schwartz, Joseph E; Shimbo, Daichi; Shikany, James M; Sims, Mario; Muntner, Paul
Abstract: BACKGROUND: Several atherosclerotic cardiovascular disease (ASCVD) risk factors are associated with awake and nocturnal hypertension. METHODS: We assessed the association between a composite ASCVD risk score and awake or nocturnal hypertension using data from participants aged 40–79 years who completed ambulatory blood pressure monitoring at the Year 30 Coronary Artery Risk Development in Young Adults study exam in 2015–2016 ( n = 716) and the baseline Jackson Heart Study exam in 2000–2004 ( n = 770). Ten-year predicted ASCVD risk was calculated using the Pooled Cohort risk equations. Awake hypertension was defined as mean awake systolic blood pressure (SBP) ≥135 mm Hg or diastolic blood pressure (DBP) ≥85 mm Hg and nocturnal hypertension was defined as mean asleep SBP ≥120 mm Hg or DBP ≥70 mm Hg. RESULTS: Among participants with a 10-year predicted ASCVD risk <5%, 5% to <7.5%, 7.5% to <10%, and ≥10%, the prevalence of awake or nocturnal hypertension as a composite outcome was 29.5%, 47.8%, 62.2%, and 69.7%, respectively. After multivariable adjustment, higher ASCVD risk was associated with higher prevalence ratios for awake or nocturnal hypertension among participants with clinic-measured SBP/DBP <130/85 mm Hg but not ≥130/85 mm Hg. The C -statistic for discriminating between participants with vs. without awake or nocturnal hypertension was 0.012 (95% confidence interval 0.003, 0.016) higher when comparing a model with ASCVD risk and clinic-measured blood pressure (BP) together vs. clinic-measured BP without ASCVD risk. CONCLUSIONS: Using 10-year predicted ASCVD risk in conjunction with clinic BP improves discrimination between individuals with and without awake or nocturnal hypertension.